Jugendliche und ihre Einstellung zur Globalisierung: Entwurf einer empirisch begründeten Typologie - Uphues, Rainer (Zeitschrift für Geographiedidaktik (ZGD), 2007)
Globalisation is one of the mostly discussed processes right now. It is necessary to know students’ attitude towards this process to improve contemporary teaching concepts. To raise the efficiency of these concepts they need to be connected to students’ realities. This article describes the contents and the methodology of an empirical poll among more than 1,000 students. Basing on these results, it is possible to develop a typology of attitudes among students. Three types can be seen: the global-conscious type, the global-indifferent type and the global-cognitive type of attitude towards globalisation. Furthermore, this poll is the foundation for didactical and methodological recommendations. Considering those it is possible to individualize everyday teaching processes.